Use of Surface Acoustic Wave (SAW) for Thermal Conductivity Sensing of Gases – a Review. Issue 6 (2nd November 2021) - Durani, Fahim; Mainuddin,; Mittal, Upendra; Kumar, Jitender; Nimal, A.T.
Abstract : This paper presents a review on the use of SAW for thermal conductivity sensing of gases. Uncoated SAW device is used as a sensing element by exploiting its high temperature sensitivity. The device is heated to a high temperature (100–150°C) and is exposed to a flow of gases at ambient temperature. Due to the temperature gradient there is a heat loss from the device resulting in temperature drop. As the quantum of heat loss depends on the thermal conductivity of the gas, the resultant variation in temperature is a measure of heat capacity of the gas. The paper brings out key advantages of SAW device for thermal conductivity-based sensing. Various SAW substrate materials are compared and their suitability for thermal conductivity application is discussed. Design considerations are discussed and validated with actual design and fabrication of SAW device. Experimental results are also presented for different flow rates of N2 and for mixture combinations of N2 and H2 at constant flow. Various limitations, particularly selectivity, are discussed towards the end and their solutions are also explored. The future trends involving Lamb Wave devices and passive sensing are also discussed.